Detection of Mycobacterium ulcerans by the loop mediated isothermal amplification method. - Anthony Ablordey; Diana Ackon Amissah; Isaac Frimpong Aboagye; Ben Hatano; Toshio Yamazaki; Tetsutaro Sata; Koichi Ishikawa; Harutaka Katano (PLoS Neglected Tropical Diseases, 2012)
BACKGROUND: Buruli ulcer (BU) caused by Mycobacterium ulcerans (M. ulcerans) has emerged as an important public health problem in several rural communities in sub-Saharan Africa. Early diagnosis and prompt treatment are important in preventing disfiguring complications associated with late stages of the disease progression. Presently there is no simple and rapid test that is appropriate for early diagnosis and use in the low-resource settings where M. ulcerans is most prevalent. METHODOLOGY: We compared conventional and pocket warmer loop mediated isothermal amplification (LAMP) methods (using a heat block and a pocket warmer respectively as heat source for amplification reaction) for the detection of M. ulcerans in clinical specimens. The effect of purified and crude DNA preparations on the detection rate of the LAMP assays were also investigated and compared with that of IS2404 PCR, a reference assay for the detection of M. ulcerans. Thirty clinical specimens from suspected BU cases were examined by LAMP and IS2404 PCR. PRINCIPAL FINDINGS: The lower detection limit of both LAMP methods at 60°C was 300 copies of IS2404 and 30 copies of IS2404 for the conventional LAMP at 65°C. When purified DNA extracts were used, both the conventional LAMP and IS2404 PCR concordantly detected 21 positive cases, while the pocket warmer LAMP detected 19 cases. Nine of 30 samples were positive by both the LAMP assays as well as IS2404 PCR when crude extracts of clinical specimens were used. CONCLUSION/SIGNIFICANCE: The LAMP method can be used as a simple and rapid test for the detection of M. ulcerans in clinical specimens. However, obtaining purified DNA, as well as generating isothermal conditions, remains a major challenge for the use of the LAMP method under field conditions. With further improvement in DNA extraction and amplification conditions, the pwLAMP could be used as a point of care diagnostic test for BU.